Comparative in vitro activities of selected antimicrobial agents against Edwardsiella tarda. - Reinhardt, J F (1985)
MICs of 14 antimicrobial agents for 29 strains of Edwardsiella tarda were determined by an agar dilution method. Of the agents tested, ciprofloxacin, enoxacin, and norfloxacin were the most active on a weight basis. All strains were also susceptible to clinically achievable concentrations of ampicillin, chloramphenicol, tetracycline, trimethoprim, sulfamethoxazole, trimethoprim plus sulfamethoxazole, cefotaxime, and gentamicin. Ninety percent of the strains demonstrated high-level resistance to polymyxin B and colistin.